From tree to paper - Marshall, Pam. (Minneapolis : Lerner Publications, 2013)
Examines the process of making paper, from wood to pulp to rolls of paper.
Workers plant trees -- Workers cut the trees -- A machine takes off bark -- The logs are chopped -- The wood is washed -- Water drips down -- The paper is dried -- The paper is rolled -- The paper is cut.
Grades K to 3.
Includes index.
Keywords: Paper; Papermaking; Lumber and lumbering